'What is to be Done?': Grammars of Organisation. Issue 2 (May 2018) - Kelly, Susan
Abstract : The question 'what is to be done?' is most often uttered at moments of great urgency and political crisis. It operates in a divide between theory and practice, when thinking should end, and action must proceed. This article considers how the grammar of this question produces relationships between subjects, action and the future, drawing a relationship between the constituent grammar of the question and Gilles Deleuze and Félix Guattari's notion of the collective assemblage of enunciation. For Deleuze and Guattari, the collective assemblage of enunciation denotes amongst other things an immanent relationship between language and action: a relationship in which politics and language are bound together in a relationship of forces. This approach aims to rethink the urgency and force that is associated with the question through examining and re-proposing the connection between the linguistic organisation of the question and the different forms of political organisation that the question might produce. In so doing, Deleuze and Guattari provide a conceptual and linguistic apparatus for rethinking the plane of political action and organisation.